The role of agri-environmental contracts in saving biodiversity in the post-socialist Czech Republic - Jaroslav Prazan; Insa Theesfeld (International Journal of the Commons, 2014)
Agri-Environmental Schemes are a voluntary policy measure of the Common Agricultural Policy of the European Union. Since 2004, these have been implemented in the post-socialist new Member States. Agri-Environmental Schemes could help to achieve a higher level of biodiversity in protected landscapes. In particular, we analyse whether such types of contract between farmers and state organisations represent a useful tool in the protection of shared natural resources, such as biodiversity. We analyse the determinants that allow for such a policy to be implemented more successfully. In addition, the administrative structure of such a policy measure is very complex since responsibilities overlap among various administrative units, and transactions between farmers and government need to be regulated. Therefore, institutional cooperation among so many parties is challenging. We analyse why implementation has been easier in some Protected Landscape Areas (PLAs) than in others. The research focuses on selected factors which showed differences in performance. In particular, these factors are trust and reciprocity between farmers and state administrative bodies, information spreading and the availability of advisory services. Despite the demanding process, we find an indication that trust tends to grow following a previous good experience. The case study was carried out in two large and two small PLAs in the Czech Republic.
Keywords: 330; agri-environmental measure; biodiversity; policy implementation; governance structure; trust; coordination problem